A Calcium Alginate Hydrogel Microsphere‐Based Transcatheter Arterial Viroembolization Strategy for Hepatocellular Carcinoma. Issue 4 (2nd January 2023) - Lv, Peng; Chen, Hu; Cheng, Hongwei; Liu, Xuan; Liu, Chao; Zeng, Yun; Jiang, Lai; Wang, Xiaoyong; Mao, Jingsong; Liu, Gang
Abstract: Oncolytic adenoviruses (OAs)‐based virotherapy can regulate the tumor microenvironment, providing a rational strategy for combination treatment with other tumor therapy techniques, such as transcatheter arterial embolization (TAE). Here, a novel, validated transcatheter arterial viroembolization (TAVE) strategy—a calcium alginate hydrogel microsphere with OA encapsulated (OA@Alg beads) to achieve a combination of TAE with oncolytic virotherapy to enhance and prolong antitumor efficacy of OA in hepatocellular carcinoma treatment—is described. The OA@Alg beads show excellent vascular embolization in a rabbit hepatic VX2 carcinoma model, resulting in successful occlusion of hepatic arteries. Importantly, OA@Alg beads enable sustained release of OA and maintain their bioactivity for extended periods while preventing OA shedding from the tumor site to healthy tissues. Moreover, the system preserves the OA's ability to induce an antitumor immune response, resulting in higher intratumoral infiltration by CD4 + /CD8 + T cells. The OA@Alg beads have the potential as an effective embolic system for TAVE in the clinical treatment of hepatocellular carcinoma. Abstract : This article presents a novel, validated transcatheter arterial viroembolization strategy: a calcium alginate hydrogel microsphere with oncolytic adenoviruses (OAs) encapsulated to achieve a combination of transcatheter arterial embolization with oncolytic virotherapy to enhance and prolong antitumor efficacy of OA in hepatocellular carcinoma treatment, which have the potential as an effective embolic system for clinical cancer treatment.